Assessment of affective domain by open ended laboratory approach in structural and material laboratory course - Jumali, Saiful; Sharipudin, Siti Shahidah; Ismail, Herda Balqis; Mohamed Ibrahim, Mohd Johan; Hasbullah, Mohd Amran (UiTM Cawangan Johor, 2021)
The objective of this study is to improve the development of affective domain among students with the introduction of the Open-Ended Laboratory (OEL). This enables students to design and conduct experiments, as well as to analyse and interpret data in a groups. By conducting the laboratory exercises in a group, students shall develop the ability to function effectively as a leader, as well as an effective team member. The present paper describes the assessment of the affective domain in OEL of Structural and Material Laboratory course for Diploma Program. This study involved a group of second-year students of Diploma of Civil Engineering/or March-July 2019 semester who enrolled in the Structural and Material Laboratory course. There were ten groups involved in this study with the total number of 233 students; 98 male and 135 female. The attainment of affective domains among students in the evaluation rubrics was investigated in discovering the effectiveness of the course assessment. Not many differences in affective domain attainment between genders are reported females shes better performance in punctuality and discipline attributes as compared to males. The outcome of this study is to observe that the OEL approach creates positive impacts in developing student generic skills such as leadership, communication, and teamwork. This attribute is expected by the industry, thus this also contributes to the overall students' learning experience.